Optimizing industrial and domestic water consumption efficiency for sustainable growth through data envelopment analysis - Z. Bayat; J. Vives Costa; J.J. de Felipe Blanch (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Water resources are essential for socio-economic development and quality of life, but limited availability, especially in regions with uneven distribution, poses challenges. Catalonia, due to fast-paced economic development, is under immense pressure from water scarcity issues, highlighting the need for efficient resource management. The objectives of the current study were to evaluate the existing water resource consumption efficiency in key sectors across Catalonia and suggest workable strategies for water management to ensure sustainability.METHODS: The water resource consumption efficiency of 42 Catalan regions in 2021 was analyzed using 50 data envelopment analysis models, employing both constant and variable returns to scale. Gross domestic product and water consumption information was acquired from regional governmental sources. The analysis included input and output-oriented models to identify opportunities for efficiency improvement.FINDINGS: The results showed that Barcelona’s industrial sector achieved optimal water resource consumption efficiency with a score of 1 in both models, setting a benchmark. Ribera d’Ebre reached full efficiency in domestic water consumption with a score of 1. Conversely, regions such as Priorat, Terra Alta, and Barcelona showed inefficiencies, suggesting that to achieve full efficiency, Priorat, Terra Alta, and Barcelona could reduce inputs by approximately 63 percent, 44 percent, and 26 percent, respectively, or increase outputs by approximately 172 percent, 78 percent, and 36 percent respectively, holding other factors constant.CONCLUSION: Targeted efficiency improvements in lower-scoring regions can contribute significantly to sustainable water management in Catalonia. Adopting successful practices observed in benchmark regions could enhance water resource management, supporting economic resilience and environmental sustainability.